Glossary to Support Applied International Research on Decision Making for High Conflict Urban Marches and Parades - Hauff, Liane; Heckmann, Thibaut (Collective Dynamics, 2021)
This article was created in context of OPMoPS (Organized Pedestrian Movement in Public Spaces), a French-German interdisciplinary collaboration on high conflict urban marches and parades. As OPMoPS aims to support decision making for authorities of public order, both a French and a German police institution are members of the consortium. Communication with target group was insofar challenging, as their experts' language is close to everyday terms. Thus the authors are proposing the following glossary to support applied international research in this field. Both authors are not skilled language experts but pragmatic members of OPMoPS's police institutions. All terms can be found in English, German and French, with a focus on police and on German police procedure. It is firstly classed in thematic order, and secondly in alphabetical order.